Spectrophotometric Estimation of Celecoxib from Capsule Formulation - Pillai, S.; Singhvi, I. (Asian Journal of Chemistry, 2010)
Two simple and sensitive spectrophotometric methods have been developed for the quantitative estimation of celecoxib from its capsule formulation. The first developed method is a UV spectrophotometric method using methanol as solvent; the drug showed absorption maxima at 253.2 nm in methanol and linearity was observed in the concentration range of 5–15 μg/mL. The second developed method is a visible spectrophotometric method, based on formation of red coloured complex of drug with 1,10-phenanthroline and ferric chloride, the complex showed absorbance maxima at 509.2 nm and linearity was observed in the concentration range of 50–400 μg/mL. Results of analysis for both the developed methods were validated statistically and by recovery studies.